Dreptul la procreare – varietate de afirmare a drepturilor reproductive ale omului [Articol] - Guceac, Ion (CEP USM, 2023)
The key element of this study builds on the recognition that family and children are of crucial importance for the development of our state. In turn, the state should take enhanced action in order for families to be built and to fulfil their obligations, including ensuring the right to procreate and increasing the birth rate. One of the measures designed to ensure qualitative changes in the demographic aspect is considered to be the promotion of the right to procreation in the legislation of the Republic of Moldova. Given that neither legislation nor policy documents are marked by the role of new technologies in the field of medicine, biological technologies and innovations, nor do they determine certain objectives or actions directly dedicated to the promotion of the right to procreation in legislation, we consider that the legal doctrine of the Republic of Moldova is obliged to support the legislator in the elaboration of scientifically based recommendations and regulations which will ensure the realisation of the right to procreation.
Keywords: human rights; right to family; right to life; reproductive behaviour